Social Media And Political Participation In Pakistan - Shahzad, Sobia (2018)
Political participation is considered a key factor for well-functioning democracy. Past studies, however, suggest a declining trend of citizen participation in politics, especially among youth, in many parts of the world. Recent evidence found the popularity of social media has contributed to participatory politics as people are increasingly exposed to political news via social media. The current study develops an integrated model of social media use and political participation to test its role in promoting political participation in Pakistan.